Mortality salience reduces attentional bias for fear-relevant animals - MacDonald, G.; Lipp, Ottmar (2008)
This research investigated the influence of reminders of mortality on biased attention for fear-relevant animals across 2 studies. In each study, participants completed a baseline dot-probe test of attention to fear-relevant animals (snakes and spiders). After random assignment, participants completed a mortality salience or control writing task (about watching television in Study 1 and about writing an important exam in Study 2). Finally, participants completed the dot-probe measure a second time. In both studies, those in the mortality salience condition showed a significant reduction in bias for fear-relevant animals from baseline to post-manipulation, whereas no change was found for those in the control conditions. These data suggest that the previously demonstrated lack of emotional response to mortality salience may, in part, result from the avoidance of fear-relevant stimuli. © 2008 Springer Science+Business Media, LLC.